Preoperative Assessment Prior to Lung Resection: How to Eliminate the Risk - Dian Megawati; Menaldi Rasmin; Budhi Antariksa; Faisal Yunus (Respiratory Science, 2022)
Lung resection is part of the treatment of various lung diseases, both malignancy and infection. Although it has great benefits, lung resection can result in a variety of functional disorders that can affect the whole cardiopulmonary system. The mortality of these procedures is 2-4% in segmentectomy and 6-8% in lobectomy, while the mortality of pneumonectomy in the world is 11%. Good preoperative assessment of patients has been reported to have reduced mortality and morbidity after lung resection. Things that need to be considered to assess preoperative eligibility include age, lung function, cardiovascular fitness, nutrition, and performance status. The preoperative pulmonary tolerance assessment is divided into three stages: the first stage is the assessment of lung function and blood gas analysis, the second stage is to assess postoperative prediction of pulmonary function, and the third stage is to assess the maximum oxygen consumption per minute by doing a cardiopulmonary exercise test. Patients who have a good tolerance for lung resection are patients who have predictive postoperative force expiration volume one second (ppoFEV1) values more than 40%, predictive postoperative diffusion capacity of the lung for carbon monoxide (ppoDLCO) more than 50%, and maximum oxygen consumption (VO2 max) more than 15ml/kg/min.